Peripheral Delta Opioid Receptors Mediate Formoterol Anti-allodynic Effect in a Mouse Model of Neuropathic Pain - Ceredig, Rhian Alice; Pierre, Florian; Doridot, Stéphane; Alduntzin, Unai; Hener, Pierre; Salvat, Eric; Yalcin, Ipek; Gaveriaux-Ruff, Claire; Barrot, Michel; Massotte, Dominique (Frontiers in Molecular Neuroscience, 2020)
Neuropathic pain is a challenging condition for which current therapies often remain unsatisfactory. Chronic administration of beta2 adrenergic agonists, including formoterol currently used to treat asthma and chronic obstructive pulmonary disease, alleviates mechanical allodynia in the sciatic nerve cuff model of neuropathic pain. The limited clinical data currently available also suggest that formoterol would be a suitable candidate for drug repurposing. The antiallodynic action of beta2 adrenergic agonists is known to require activation of the delta opioid (DOP) receptor but better knowledge of the molecular mechanisms involved is necessary. Using a mouse line in which DOP receptors were selectively ablated in neurons expressing Nav1.8 sodium channels (DOP cKO), we established here that these DOP peripheral receptors were mandatory for the antiallodynic action of the beta2 adrenergic agonist formoterol in the cuff model. Using a knock-in mouse line expressing a fluorescent version of the DOP receptor fused with the enhanced green fluorescent protein (DOPeGFP), we showed in a previous study, that mechanical allodynia is associated with a reduced proportion of DOPeGFP positive small peptidergic sensory neurons in dorsal root ganglia, with a lower density of DOPeGFP positive free nerve endings in the skin and with increased DOPeGFP translocation to the plasma membrane. Here, we showed that the density of DOPeGFP positive free nerve endings in the skin is partially restored and no increase in DOPeGFP translocation to the plasma membrane is observed in mice in which mechanical pain is alleviated upon chronic oral administration of formoterol. This study therefore extends our previous results by confirming that changes in mechanical threshold are associated with changes in peripheral DOP profile. It also highlights common impact on DOP receptors between serotonin noradrenalin reuptake inhibitor such as duloxetine and the beta2 mimetic formoterol.